Exploring the Unique Stylistics and Divine Rhetoric of the Qur'an: Unveiling the Linguistic Miracle of Revelation - M. Shofiyyur Rahman Hawary; Riadi Banjarnaor; Muhammad Ridwan; M. Akil Fathur Rahman Syah; Agustiar Agustiar (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
This article explores the unique stylistic features and divine rhetoric of the Qur'an, offering a fresh perspective on how the linguistic beauty of the sacred text functions as an essential aspect of its miraculous nature. The study aims to uncover how the Qur'an employs various rhetorical strategies and language styles not merely as literary embellishments, but as powerful tools to convey messages of monotheism, morality, law, and spirituality. Using a library research method with a descriptive-qualitative approach, the analysis focuses on selected verses that demonstrate stylistic elements such as al-qashr (exclusivity), at-taqdim wa at-ta’khir (word order inversion), isti‘arah (metaphor), tibaq (antithesis), saj‘ (rhymed prose), and rhetorical devices like qasam (oath), takrar (repetition), and istifham (rhetorical question). The findings reveal that the Qur'an's linguistic structure is not only aesthetically captivating but also deeply persuasive, intellectually engaging, and emotionally resonant. The main contribution of this study lies in affirming that the Qur’an’s linguistic beauty is an inseparable component of its divine miracle, positioning stylistic and rhetorical analysis as a meaningful and modern interpretative tool in Qur’anic studies.